85.6k views
4 votes
How to solve this?:

2x+2y=9
2x-y=3

2 Answers

5 votes

Answer:

(2.5, 2 )

Explanation:

Given the 2 equations

2x + 2y = 9 → (1)

2x - y = 3 → (2)

Rearrange (2) expressing y in terms of x

y = 2x - 3 → (3)

Substitute y = 2x - 3 into (1)

2x + 2(2x - 3) = 9 ← distribute left side and simplify

2x + 4x - 6 = 9

6x - 6 = 9 ( add 6 to both sides )

6x = 15 ( divide both sides by 6 )

x = 2.5

Substitute x = 2.5 into (3) for corresponding value of y

y = 2(2.5) - 3 = 5 - 3 = 2

Solution is (2.5, 2 )

User Logcat
by
5.3k points
6 votes

Solve this using the elimination process.

They're already lined up so just solve!

2x + 2x = 4x

2y+ (-y) = 3y

9 + 3 = 12

4x + (-1y) = 12

Now solve.

4x + -1 x y = 12

4x - y = 12

4x = 12 + y

x = 12 + y / 4

First, when a problem is lined up with the same vales/terms, you can use the elimination process while doing math.

Then, make your equation by adding and subtracting the same terms.

Therefore, you finally get your answer.

Keep in mind not all answers will be a full number.

User Drogba
by
5.9k points